Diagnosis of the invasiveness of lung adenocarcinoma manifesting as ground glass opacities on high‐resolution computed tomography. Issue 1 (27th April 2015) - Mao, Haixia; Labh, Kanchan; Han, Fushi; Jiang, Sen; Yang, Yang; Sun, Xiwen
Abstract: Background: To explore the diagnostic method in assessing the malignancy of pulmonary adenocarcinoma characterized by ground glass opacities (GGO) on computed tomography (CT). Methods: Preoperative CT data for preinvasive and invasive lung adenocarcinomas were analyzed retrospectively. GGO lesions that were detected on lung windows but absent using the mediastinal window were subject to adjustment of the window width, which was reduced with the fixed interval of 100 HU until the lesions were no longer evident, with a fixed mediastinal window level of 40 HU. The shape, smoking habits, size of the lesion on the lung window, and window width at which lesions disappeared were compared and receiver operating characteristic curves were used to determine the optimal cut‐off of the lesion size and window width to differentiate between these invasive and preinvasive lesions. Results: Of the 209 lung adenocarcinomas, 102 were preinvasive (25 atypical adenomatous hyperplasia and 77 adenocarcinoma in situ), while 107 were invasive (78 minimally invasive adenocarcinoma and 29 invasive adenocarcinoma). The shape, lesion size, and window width at which lesions were no longer evident differed significantly between the two groups ( P < 0.05). The size of 8.9 mm and a window width of 1250 HU were the optimal cut‐off to differentiate between preinvasive and invasive lesions. Conclusion: The shape, size of the lesion, and window width on high‐resolution CT may be useful in assessing the invasiveness of lung adenocarcinoma that manifests as GGO. Irregular lesions that disappear at window width <1250 HU, with a diameter of > 8.9 mm are more likely to be invasive.